Emerging Market Brands : Malaysian Consumers’ Perception - Ng, Qi Hui (2012)
Purpose – The purpose of this dissertation is to explore consumer attitudes towards emerging market brands by using factors like Country of origin, product quality and social influence. A model including the above factors will be used to evaluate the consumer behaviour. Design/methodology/approach – Malaysia is the country chosen for the study. A total of 82 questionnaires are distributed mostly in the Johor Bahru area using close-end questionnaires. Findings – It was found that product quality emerged as the main factor in influencing the perception of Malaysian consumers. Most consumers are not prejudiced against emerging market brands but they are prejudiced towards China‘s emerging market brands. Country of origin and social influence do not play a significant role in influencing the consumers‘ perception. Research Limitations / implications – This study enhances the knowledge about consumer behaviour and their perceptions of emerging market brands in Malaysia. Managerial Implications – For emerging market brands to get a foothold in Malaysia, marketers must possess a thorough understanding of the characteristics of the Malaysia market, her multi-ethnic society and the impact of the volatile world economy on Malaysian consumers for the emerging market brands to grow as different knowledge has to be applied to different context.